2015
DOI: 10.1093/intimm/dxv060
|View full text |Cite
|
Sign up to set email alerts
|

CD3ε recruits Numb to promote TCR degradation

Abstract: Modulation of TCR signaling upon ligand binding is achieved by changes in the equilibrium between TCR degradation, recycling and synthesis; surprisingly, the molecular mechanism of such an important process is not fully understood. Here, we describe the role of a new player in the mediation of TCR degradation: the endocytic adaptor Numb. Our data show that Numb inhibition leads to abnormal intracellular distribution and defective TCR degradation in mature T lymphocytes. In addition, we find that Numb simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Constitutive expression of CD69 and interferon‐ γ , as well as constitutively phosphorylated ERK, are found in the CD4 + T cells from dominant negative Numb transgenic mice. Upon stimulation, CD4 + T cells from these mice exhibit higher ERK, ZAP‐70 and Akt phosphorylation than those of the wild‐type mice, indicating that Numb may be required for a negative control of TCR‐mediated signal transduction . It was suggested that Numb plays a role in TCR degradation by simultaneously binding to both Cbl and a site within CD3 ε that overlaps with the Nck binding site, thus mediating TCR degradation …”
Section: Numbmentioning
confidence: 99%
See 3 more Smart Citations
“…Constitutive expression of CD69 and interferon‐ γ , as well as constitutively phosphorylated ERK, are found in the CD4 + T cells from dominant negative Numb transgenic mice. Upon stimulation, CD4 + T cells from these mice exhibit higher ERK, ZAP‐70 and Akt phosphorylation than those of the wild‐type mice, indicating that Numb may be required for a negative control of TCR‐mediated signal transduction . It was suggested that Numb plays a role in TCR degradation by simultaneously binding to both Cbl and a site within CD3 ε that overlaps with the Nck binding site, thus mediating TCR degradation …”
Section: Numbmentioning
confidence: 99%
“…Upon stimulation, CD4 + T cells from these mice exhibit higher ERK, ZAP-70 and Akt phosphorylation than those of the wild-type mice, indicating that Numb may be required for a negative control of TCR-mediated signal transduction. 84 It was suggested that Numb plays a role in TCR degradation by simultaneously binding to both Cbl and a site within CD3e that overlaps with the Nck binding site, thus mediating TCR degradation. 84 Numb can bind with its phosphotyrosine binding domain to the cytoplasmic tail of CD3e within the PRS to the sequence NPDY.…”
Section: Numbmentioning
confidence: 99%
See 2 more Smart Citations
“…TCR-CD3 complex assembly is initiated by forming two heterodimers CD3D/CD3E and CD3G/CD3E. It also participates in the internalization of TCR-CD3 complexes and cell surface down-regulation by endocytic sequences present in the cytoplasmic region of CD3E [40][41][42]. The relationship between the abundance of tumor in ltrating lymphocytes and the expression, copy number, methylation or mutation of CD3E in LGG was shown in Supplement Fig.…”
Section: Discussionmentioning
confidence: 99%